Between Policy and Practice: Teachers’ Lived Narratives of Deep Learning Implementation, Classroom Interaction, and Learning Transformation in Indonesian Elementary Education - Hani Subakti; Nurul Hikmah; Eka Selvi Handayani; Euis Kusumarini; Wiwik Angranti; Abror Nusaf Mujaddid (Yayasan Adra Karima Hubbi, 2026)
Background. The implementation of deep learning, character-based pedagogy, and digital transformation has become an important agenda in improving the quality of Islamic Religious Education in elementary schools. However, the translation of policy into classroom practice often depends on teachers’ readiness, pedagogical understanding, digital competence, and school-level support. Purpose. This study aims to explore teachers’ experiences in bridging educational policy and classroom practice through the strengthening of deep learning, character-based pedagogy, and the digital transformation of Islamic Religious Education in elementary schools. Method. This study employed a qualitative research design. Data were collected through semi-structured interviews, classroom observations, and document analysis involving Islamic Religious Education teachers at the elementary school level. The data were analyzed thematically to identify patterns related to deep learning practices, character formation, digital integration, and implementation challenges. Results. The findings indicate that teachers understand deep learning as a process of promoting meaningful understanding, reflection, critical engagement, and the internalization of Islamic values. Character-based pedagogy is implemented through habituation, moral exemplification, classroom dialogue, and the integration of religious values into daily learning activities. Digital transformation supports Islamic Religious Education through multimedia resources, interactive learning platforms, and online assessment tools. However, its implementation is constrained by limited infrastructure, varying levels of digital literacy, unequal access to technology, and insufficient professional development. Conclusion. The study concludes that the successful transformation of Islamic Religious Education requires stronger alignment between policy expectations and classroom realities. Continuous teacher training, institutional support, adequate digital infrastructure, and context-sensitive pedagogical strategies are essential to strengthen deep learning, character formation, and digital integration in elementary Islamic Religious Education.